Ginseng - Modern Aspects of the Famed Traditional Medicine 2022
DOI: 10.5772/intechopen.99646
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng: Pharmacological Action and Phytochemistry Prospective

Abstract: Ginseng, the root of Panax species is a well-known conventional and perennial herb belonging to Araliaceae of various countries China, Korea, and Japan that is also known as the king of all herbs and famous for many years worldwide. It is a short underground rhizome that is associated with the fleshy root. Pharmacognostic details of cultivation and collection with different morphological characters are discussed. Phytocontent present is saponins glycosides, carbohydrates, polyacetylenes, phytosterols, nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The antifatigue properties of herbals are associated with secondary metabolites that they contain. Authors which have evaluated anti-fatigue potential of herbal, has sought to know and identified the different groups of phytochemicals metabolites (polyphenols, terpenoids, saponins and alkaloids, saponins glycosides, polyacetylenes, phytosterols) which could lead to improvement of athletic performance and reducing fatigue [9,84].…”
Section: Secondary Metabolites With Anti-fatigue Propertiesmentioning
confidence: 99%
“…The antifatigue properties of herbals are associated with secondary metabolites that they contain. Authors which have evaluated anti-fatigue potential of herbal, has sought to know and identified the different groups of phytochemicals metabolites (polyphenols, terpenoids, saponins and alkaloids, saponins glycosides, polyacetylenes, phytosterols) which could lead to improvement of athletic performance and reducing fatigue [9,84].…”
Section: Secondary Metabolites With Anti-fatigue Propertiesmentioning
confidence: 99%
“…P. ginseng , commonly known as Asian ginseng, Chinese ginseng, or Korean ginseng, is also a perennial plant that belongs to the Araliaceae family (Ratan et al, 2021). P. ginseng is native to China, Korea, and Siberia and has been used for centuries in traditional medicine (Mehta et al, 2021). Ginseng is a very researched herb; there is a copious amount of data available in the Journal of Ginseng Research and other journals.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides are the main chemical constituent of P. ginseng and exhibit antioxidant, anti-inflammatory, and even anticancer potential. Polysaccharides and flavonoids present in ginseng exhibit immunomodulating properties and may help to protect against oxidative stress (Kim, 2018; Mehta et al, 2021). In terms of its phytochemical and nutritional profile, P. ginseng is rich in vitamins and minerals like vitamins B 1 , B 2 , B 12 and calcium, iron, potassium, and so on (Kang & Kim, 2016; Kim et al, 2018; Lee, et al, 2019; Lee & Kim, 2014; Mehta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations